Pelatihan Foto Produk Pada UMKM Bu Erni Di Desa Mojotengah Kecamatan Bareng Kabupaten Jombang - Allya Almuqrhoina Fajri; Regita Ayudhea Permata Putri; Agus Widiyarta (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
Photography has developed so that it has progressed and has become one of the important needs for human lives Photography can open opportunities in the business world, one of which is to support product marketing. Mojotengah is one of the villages in the Bareng District, Jombang Regency. Mojotengah Village which offers high quality local products made by MSMEs. The problem that arises in this case is the lack of skills of MSME actors in taking attractive photos of their products. Apart from that, due to the lack of interesting tools or properties in taking photos. This product photo training was held with the aim of improving participants' ability to take product photos correctly so as to attract more buyers' attention. This product photo training uses the PALS method and is carried out in several steps .Then these MSMEs create social media accounts for marketing purposes and product photos are then advertised on social media accounts belonging to MSME actors. The results obtained from this training were that this training was enthusiastically attended by MSME actors and there was an increase in product sales because the results of new product photos managed to attract the attention of more buyers. Photography has developed so that it has progressed and has become one of the important needs for human lives Photography can open opportunities in the business world, one of which is to support product marketing. Mojotengah is one of the villages in the Bareng District, Jombang Regency. Mojotengah Village which offers high quality local products made by MSMEs. The problem that arises in this case is the lack of skills of MSME actors in taking attractive photos of their products. Apart from that, due to the lack of interesting tools or properties in taking photos. This product photo training was held with the aim of improving participants' ability to take product photos correctly so as to attract more buyers' attention. This product photo training uses the PALS method and is carried out in several steps .Then these MSMEs create social media accounts for marketing purposes and product photos are then advertised on social media accounts belonging to MSME actors. The results obtained from this training were that this training was enthusiastically attended by MSME actors and there was an increase in product sales because the results of new product photos managed to attract the attention of more buyers.